Communities of the association Sagino procumbentis– Bryetum argentei Diemont et al. 1940 in urban ecosystems of Pyryatyn (Poltava region) and Kyiv (CHORNOMORSKI BOTANICAL JOURNAL, 2013)
The communities of the association Sagino procumbentis–Bryetum argentei Diemont et al. 1940 in urban ecosystems of Pyryatyn (Poltava region) and Kyiv are studied. The typical and new subassociations S.-B. marсhanthietosum polymorphae Kovalenko 2013 subass. nova are distinguished. This syntaxa are floristically, coentically and physiognomically distinct. The subassociations are different in dimension of ecology factors. The features of ecology, phenology, coenotic, biomorphological and geographical structures of the association make a problem of including association Sagino procumbentis–Bryetum argentei in system of high-level syntaxa. In results of floristic parsimony of phytocoenons from Isoëto-Nano-Juncetea and Polygono–Poëtea annuae classes the need of including association in system of the last classes is outlined.
Keywords: vegetation of urban ecosystems, Sagino procumbentis–Bryetum argentei, Saginion procumbentis, Polygono–Poëtea annuae.